Third-party artificial insemination and the problem of donating sperm and eggs - A comparative study between the Algerian law, Islamic law, French law and European laws in general - Souiki, H’oriya (Technium Social Sciences Journal, 2022)
The progress of science in the medical field and the legal framing of artificial insemination have engendered the problem of third-party insemination in accordance with a legal framework that is provided by some countries. This mainly aims to guarantee the right to every person unable to procreate to have children. This situation led to the creation of sperm and egg banks which began to receive donations, free of charge, while protecting the confidentiality of donor-related information. The importance of the topic pushed us to carry out a comparative study in order to clarify the stance of the Algerian legislator on this issue, with respect to Islamic Law or Sharia, and then to discuss the legal framing of the sperm and egg donation process in the French and European laws. We also try to examine the way these countries address the most significant pressures they are exposed to from the children born by this method considering their right to know their lineage.